Bilingual Learning Program in Math and Science Subject for Junior High School: An Evaluation using CIPP Model - Mentari, Rafinda Putri; Jaedun, Amat; Widyastuti, Puspa; Safitri, Rina (Jurnal Pendidikan Progresif, 2024)
Abstract: Bilingual Learning Program in Math and Science Subject for Junior High School: An Evaluation using CIPP Model. Objective: The current research was to reveal the implementation of bilingual learning programs at private junior high schools in D.I. Yogyakarta in terms of context, input, process, product. Methods: A descriptive quantitative approach was implemented to 52 students that was chosen by purposive sampling. Data collection used questionnaires, observations and interviews that was analyzed in terms of content validity, construct validity, reliability, and percentage of success. Findings: The context component is in accordance with the school's vision, mission, goals and curriculum, the input component of Budi Mulia Dua Middle School with a percentage of 74% is in the good category, Mutiara Persada Middle School with a percentage of 62% is in the good category, Growing Middle School with a percentage of 78% is in the good category, Component process Budi Mulia Dua Middle School with a percentage of 70% in the good category, Mutiara Persada Middle School with a percentage of 77.5% in the good category, Growing Middle School with a percentage of 79% in the good category. The product component shows that the results of the bilingual class are higher than the national class. Conclusion: Evaluation of the CIPP model bilingual learning program has gone well. This can be seen from the results of the context, input, process and product components. Kata kunci: bilingual learning program, CIPP evaluation model, junior high school students.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202410